Exploitation patterns of the multi species/gear hake (Merluccius capensis and paradoxus) fishery on South Africa's southeast coast - Sutton, Glen Robert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2000)
The motivation for this study was to examine the exploitation patterns of the M. capensis and M. paradoxus hake fisheries on the Southeast Coast, and determine the size and species of hake caught in each of the hand-line, long-line, and trawl methods. The handline hake fishery has increased substantially over the last several years and concerns are beginning to emerge about the impact this will have on the inshore resource collected on the South Coast between August 1998 and July 1999 was used to describe the hand-line method and estimate annual landings. Data on the size and species in longline catches of hake caught during 1997 were already available for this study. Size distributions in trawl catches were determined from commercial category landing data reported by catch weight and depth. The species composition in these catches determined by comparison using RV Afrikana survey data collected in the same depth regions. Location plays a significant role in determining the sizes and species of hake caught by each gear. Hand-lines catch smaller sizes on average than do long-lines, inshore trawls target mainly M. capensis while offshore trawls catch both hake species. A substantial amount of the hand-line hake caught on the South Coast is not reported. Examination of the exploitation patterns reveal that intense trawling pressure is directed at the smaller sized M. paradoxus inhabiting the depth region between 160-400-meters. Inshore trawls discard a large amount of small sized M. capensis within the 100-meter isobath. A preliminary stock assessment on the status of each hake species found that M. paradoxus appears to be over-exploited while M. capensis was in better shape. However, length-based pseudo-cohort analysis, used in this assessment, is critically reliant on having length frequency data from a steady state population in equilibrium. This limits the application of this model for management purposes and this finding is purely theoretical at this stage. Results suggest that each hake species is under a different pattern and level of exploitation and the multi-species nature of hake stocks on the South Coast should be considered in developing optimum management policies. Future work should focus on developing appropriate age/length keys so that an age-based VPA, which is more powerful than the length-based approach, can be applied towards stock assessments on the South Coast. Alternatively, length-data covering a longer period should be compiled and the equilibrium assumption further investigated so that the results from length-based models can be used with more confidence.
Keywords: Fishing -- South Africa; Hake -- South Africa; Merluccius capensis -- South Africa; Merluccius paradoxus -- South Africa